Debt Financing as a Structural Shield: Capital Intensity, CSR, and Tax Aggressiveness in Indonesian Manufacturing - Nur Afni Yunita; Muhammad Yusra; Sri Mulyati; Fitri Maghfirah (Winaya Inspirasi Nusantara Foundation, 2026)
Tax aggressiveness remains a persistent concern for fiscal authorities and stakeholders, as it directly diminishes public revenue and complicates regulatory compliance. While firm-level attributes such as capital intensity, leverage, and corporate social responsibility (CSR) frequently inform discussions on tax planning, empirical consensus regarding their influence remains elusive, particularly within the Indonesian manufacturing sector. This study investigates the impact of these three determinants on corporate tax aggressiveness among manufacturing entities listed on the Indonesia Stock Exchange (IDX). Utilizing a quantitative framework, we applied panel data regression analysis to a purposive sample of 93 manufacturing firms observed between 2019 and 2024. Our analysis reveals that neither capital intensity nor CSR exerts a statistically significant influence on tax aggressiveness. Conversely, leverage demonstrates a significant negative association with tax aggressive behavior. This inverse relationship suggests that firms maintaining higher debt levels benefit from substantial interest tax shields; these deductible expenses effectively lower taxable income, thereby reducing the firm's overall tax liability. These findings indicate that leverage serves as a primary mechanism for tax management in this context. Rather than pursuing aggressive avoidance strategies, highly leveraged firms appear to prioritize the inherent tax advantages derived from their financing structures. These results offer critical implications for policymakers, investors, and corporate managers navigating the intersection of capital structure decisions and fiscal compliance.